Integration of Positive Accounting Theory and Human Resource Readiness in Facing Accounting Disruption in the Society 5.0 Era (Accounting Student Case Study 2023) - Apip Alansori; Suci Amanda; Gian Qiesya Kusuma Seta; Rafa Azizah Utomo (Jurnal Ekonomi, Akutansi dan Manajemen Nusantara, 2026)
This study examines the prospects and challenges facing the accounting profession in Indonesia amidst the digital revolution, particularly in the context of Society 5.0. Accounting digitalization is understood as a holistic transformation aimed at improving the quality of life through the utilization of data and advanced technologies such as Artificial Intelligence (AI), the Internet of Things (IoT), big data analytics, and cloud computing. The concept of Super Smart Accounting and the role of Human-Centered Accountants are the primary focus in addressing the automation of repetitive tasks. While offering efficiency, productivity, and new specialization opportunities, digitalization also poses significant challenges such as a skills gap, resistance to change, privacy and cybersecurity issues, and unequal access to digital infrastructure. Digital transformation within the framework of Society 5.0 requires comprehensive changes in accounting practices, from manual systems to automation based on smart technology. This study aims to evaluate the level of readiness of accounting students in facing technological disruption and to identify the adaptation barriers faced by prospective professionals. The method used is descriptive qualitative with a literature study approach analyzed using the Miles and Huberman model and the Positive Accounting Theory and Entity Theory frameworks. The results show that although digitization increases efficiency through Super Smart Accounting, there are major obstacles in the form of a skills gap and resistance to change. Specifically, a shift in the learning behavior of students at Malahayati University was found, with a tendency to rely on digital devices instantly, thereby risking a decline in the depth of academic understanding. In conclusion, the accounting profession of the future requires the integration of data literacy and human literacy. The implication is that universities need to reform their curricula to be more adaptive and practical skills-based in order to face the challenges of the digital world of work.